2008
DOI: 10.1007/s10286-007-1004-0
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology and diagnosis of orthostatic hypotension

Abstract: Orthostatic Hypotension (OH) is a common manifestation of blood pressure dysregulation. OH takes a heavy toll on quality of life. It has many potential etiologies, and many effects of aging can increase susceptibility to OH. Neurological disorders are especially likely to cause severe OH. In this brief review, the pathogenesis of OH is considered, particularly in terms of autonomic neuropathy, multiple system atrophy (MSA), pure autonomic failure, baroreflex failure, and dopamine beta hydroxylase deficiency. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 22 publications
1
71
0
5
Order By: Relevance
“…It is known that hypertension is associated with OH (4), particularly in elderly people. One of the most important mechanisms of OH is baroreflex dysfunction, which is in part caused by baroreceptor impairment due to aging or atherosclerosis (23,24). When we used the TUG test as a measure of physical function, we found that OH was associated with a shorter time on the TUG test, with whom physical function may be relatively preserved.…”
Section: Discussionmentioning
confidence: 88%
“…It is known that hypertension is associated with OH (4), particularly in elderly people. One of the most important mechanisms of OH is baroreflex dysfunction, which is in part caused by baroreceptor impairment due to aging or atherosclerosis (23,24). When we used the TUG test as a measure of physical function, we found that OH was associated with a shorter time on the TUG test, with whom physical function may be relatively preserved.…”
Section: Discussionmentioning
confidence: 88%
“…Orthostatic hypotension (OH) is the most frequent symptom of cardiovascular autonomic dysfunction [44,50]. About 50% of PD patients with advanced disease and the majority of MSA patients complain about common symptoms of OH such as dizziness, lightheadedness, and nausea or pain during standing [7].…”
Section: Cardiovascular System: Orthostatic Hypotensionmentioning
confidence: 99%
“…Orthostatic hypotension is asymptomatic when the patient does not develop any symptoms, or is symptomatic when the patient experiences dizziness, weakness, nausea, pain or impaired vision in response to postural change. To account for symptomatic and asymptomatic orthostatic hypotension Robertson suggested the 'standing time' as practical clinical diagnostic parameter [Robertson, 2008]. Standing time is defined as the period from getting up until orthostatic symptoms occur.…”
Section: Pathophysiology Of Dysautonomiamentioning
confidence: 99%
“…Cardiovascular system: orthostatic hypotension Orthostatic hypotension is the most frequent symptom of cardiovascular autonomic dysfunction [Robertson, 2008;Peralta et al 2007]. About 50% of PD patients with advanced disease and the majority of MSA patients complain about common symptoms of orthostatic hypotension such as dizziness, lightheadedness, and nausea or pain during standing [Bleasdale-Barr and Mathias, 1998].…”
Section: Pathophysiology Of Dysautonomiamentioning
confidence: 99%